Pengaruh bahan pengisi serat kaca terhadap sifat fisik dan kristalinitas polipaduan PC/ABS - Dwi Wahini Nurhajati; Muhammad Sholeh; Ihda Novia Indrajati; Ike Setyorini (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2017)
This research aimed to determine the effects of the addition of glass fibers on the physical and crystallinity properties of PC/ABS polyblends. The ratio of PC/ABS used in this research was 75/25, while the addition of glass fibers ranged from 0; 5; 10; to 15 phr (based on the weight of PC/ABS). Polyblends of PC/ABS/glass fibers were prepared in a twin screw extruder. The test results showed that density and tensile strength of PC/ABS polyblends increased with an increase in the glass fiber content. The presence of glass fibers decreased MFI and impact strength of these PC/ABS polyblends. The functional groups were determined by the fourier transform infrared (FTIR) spectrophotometer while crystallinity was examined using X-ray diffractometer (XRD).Keywords: PC/ABS polyblend, glass fiber, physical properties, crystallinity.